2007
DOI: 10.1007/s11102-007-0066-2
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9, a potential biological marker in invasive pituitary adenomas

Abstract: MMP-9 expression can consistently distinguish invasive pituitary tumors from noninvasive pituitary tumors and would reflect the extent of invasiveness in pituitary tumors according to tumor subtype, size, tumor extension, primary and redo surgery, even at early stages of invasiveness. MMP-9 may be considered a potential biomarker to determine and predict the invasive nature of pituitary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 45 publications
4
33
0
2
Order By: Relevance
“…PTTG and MMP9 were also up-regulated in the invasive tumors, as measured by qRT-PCR (data not shown), in keeping with previous findings (Turner et al 2000, Trouillas et al 2003, Filippella et al 2006, Gong et al 2008, Hussaini et al 2007, Wierinckx et al 2007. At the protein level, PTTG staining was stronger in invasive tissues and displayed a good correlation with that of MYO5A.…”
Section: Igfbp5supporting
confidence: 90%
See 1 more Smart Citation
“…PTTG and MMP9 were also up-regulated in the invasive tumors, as measured by qRT-PCR (data not shown), in keeping with previous findings (Turner et al 2000, Trouillas et al 2003, Filippella et al 2006, Gong et al 2008, Hussaini et al 2007, Wierinckx et al 2007. At the protein level, PTTG staining was stronger in invasive tissues and displayed a good correlation with that of MYO5A.…”
Section: Igfbp5supporting
confidence: 90%
“…The role of PTTG (Zhang et al 1999, Salehi et al 2008 and the N-terminally truncated isoform of fibroblast growth factor receptor 4 (FGFR4) (ptd-FGFR4; Qian et al 2004) has been suggested. Overexpression of polysialylated neural cell adhesion molecule has been related to pituitary adenoma invasion (Trouillas et al 2003), and overexpression of matrix metalloproteases (MMPs), and particularly MMP-9, has been detected in various types of invasive adenoma (Turner et al 2000, Gong et al 2008, Hussaini et al 2007. Bone morphogenic protein, a factor involved in gonadotroph tumor development, might also play a role along with retinoic acid-inducible neural-specific protein 3 (Shorts-Cary et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…6 Alternatively, the biology of GH-secreting adenomas may enable them to more easily invade surrounding dural and/or bony structures, perhaps due to differential expression of proteins involved with degradation, such as matrix metalloproteinases. 5,7,15 Consistent with this reasoning is that GH-secreting adenomas with a more aggressive inherent tumor biology that met the WHO criteria for atypical adenomas demonstrated especially peculiar patterns of isolated extension through the sellar floor and into the clivus, comprising 5 of the 13 GH-secreting adenomas with such growth. However, nonfunctional adenomas are typically larger tumors at the time of diagnosis and tend to grow through the diaphragmatic aperture and into the suprasellar cistern without primarily invading bony structures or the cavernous sinus, until they become larger tumors.…”
Section: Discussionmentioning
confidence: 84%
“…Many researches have illustrated that MMP2 (Liu et al 2005) and MMP9 (Gong et al 2008) play important roles in pituitary tumor invasion. Both MMP2 and MMP9 are type IV collagenases, which can break down basement membrane, in particular, cleaving type IV collagen (Kawamoto et al 1996).…”
Section: Discussionmentioning
confidence: 99%